From the history of the student movement in The Arab world Strike of the students of the Syrian Evangelical College 1883-2 (Journal of the College of Basic Education, 2022)
The history of the student movement in the Arab world witnessed many forms of heroismAnd sacrifice in our modern and contemporary history.The student strike at the Syrian Evangelical College in 1882-1883.Research topic - a bright picture in the history of the student movement.The research included an overview of the history of the college and the stages of its establishment. The role of missionariesThe American missionary in its development until it became a scientific edifice that has few counterparts in the EastArabi . It also dealt with the reasons and motives that prompted the students to strike and bomb((crisis)) in the aforementioned college. The removal of Dr. Edwin Lewis from a jobteaching the immediate cause of said strike; The college dean had excluded the aforementionedAnd terminated his teaching services